Sistem Informasi Apotek Maju Bersama Menggunakan Metode Prototype Berbasis Web - Dwi nanda, fitra; Elhanafi, Andi Marwan; Irwan, Dedy (Jurnal Multimedia dan Teknologi Informasi (Jatilima), 2024)
Pharmacies are an important part of the health service system that provides medicines and health products to the public. However, many pharmacies still use manual systems in managing transaction data and stock of goods which often cause problems such as recording errors, data loss, and long processing times. This research aims to design and implement a web-based Pharmacy Management Information System at Maju Bersama Pharmacy using the prototype method. The prototype method was chosen because of its ability to allow for rapid iteration and continuous feedback from users, so that the system can be designed according to specific needs. The results of the study show that the implemented system is able to improve operational efficiency by automating the process of recording and managing data, minimizing errors, and providing more accurate and reliable information. With this system, pharmacy staff can focus more on serving customers, so that the quality of service also improves. This research is expected to be a reference in the development of management information systems in other pharmacies.